Efficacy of Vacuum-assisted Wound Closure in Improving Healing in Breast Surgery Patients: A Review - Alexa Clark, BA; James Sherrer, BS; Karina Grover, BS; Orr Shauly, MD; Daniel J. Gould, MD, PhD; Albert Losken, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Negative-pressure wound therapy (NPWT) has been shown to facilitate complex wound closure, decrease healing complications, and improve scar quality. Recently, its application in closed incision wound healing has been studied. Although relatively new to plastic surgery, outcomes and complication rates of NPWT compared with conventional dressings following breast surgery have been increasingly studied. The purpose of this study is to review the literature to evaluate the efficacy of NPWT over standard-of-care closure in breast reconstruction and aesthetic surgery. Methods:. A PubMed search was performed following Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines to assess the use of NPWT in women 18 years or older who received breast reconstruction, augmentation, or reduction surgery. After abstract, full-text, and reference review, 13 articles were evaluated, and postoperative complications, such as seroma, hematoma, and infection incidence, were extracted. Results:. Of the 10 articles that reported overall complication rates, 6 showed significant decreases in complications for breasts treated with an NPWT approach. All types of breast surgery and wound vacuum brands were used within these 6 studies. Patients who underwent breast reduction did not show a significant rise in hematoma or seroma formation with the use of NPWT. However, 2 studies reported a notable increase in seroma formation following breast reconstruction and augmentation surgery. There was no significant difference in infection rates between control and NPWT groups. Three studies primarily reporting bilateral breast reduction outcomes found a significantly decreased rate of wound dehiscence postoperatively compared with the standard dressing. Conclusions:. NPWT is a promising alternative to standard-of-care dressings for mitigating postoperative wound healing complications in breast reconstruction, augmentation, and reduction. Limitations of this review include the lack of statistical comparison due to the small number of available studies and the minimal consistency of primary outcomes reported within breast surgery research. Even so, NPWT demonstrates an overall decrease in complications and provides a novel approach to enhancing cosmesis and healing of breast incisions postoperatively.